2021
DOI: 10.1016/j.bios.2021.113588
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping assisted label-free and amplification-free detection of SARS-CoV-2 RNAs with an optofluidic nanopore sensor

Abstract: Ultrasensitive, versatile sensors for molecular biomarkers are a critical component of disease diagnostics and personalized medicine as the COVID-19 pandemic has revealed in dramatic fashion. Integrated electrical nanopore sensors can fill this need via label-free, direct detection of individual biomolecules, but a fully functional device for clinical sample analysis has yet to be developed. Here, we report amplification-free detection of SARS-CoV-2 RNAs with single molecule sensitivity from clinical nasophary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Following this principle, the authors have demonstrated an almost two orders of magnitude increase in the analyte capture rate, which in turn illustrates the efficacy of their methodology. In a separate study, the lab has demonstrated a TACRE-based amplification-free detection of SARS-CoV-2 RNAs with a capture rate enhancement of over 2000× within the entire clinically relevant concentration range from 10 4 -10 9 copies/mL [428]. Therefore, it is probably safe to say that TACRE has particular relevance in clinical diagnostics, especially at ultra-low concentrations, paving the way toward early-stage disease detection.…”
Section: Electrical Methods For Single-molecule Experimentsmentioning
confidence: 99%
“…Following this principle, the authors have demonstrated an almost two orders of magnitude increase in the analyte capture rate, which in turn illustrates the efficacy of their methodology. In a separate study, the lab has demonstrated a TACRE-based amplification-free detection of SARS-CoV-2 RNAs with a capture rate enhancement of over 2000× within the entire clinically relevant concentration range from 10 4 -10 9 copies/mL [428]. Therefore, it is probably safe to say that TACRE has particular relevance in clinical diagnostics, especially at ultra-low concentrations, paving the way toward early-stage disease detection.…”
Section: Electrical Methods For Single-molecule Experimentsmentioning
confidence: 99%
“…Yakoh et al reported a paper-based electrochemical biosensor for label-free detection of SARS-CoV-2 antibodies without the specific requirements of antibodies [ 164 ]. With optical assistance, Mohammad et al designed an electro-optofluidic chip that detected target SARS-CoV-2 RNAs without amplification, the detection limits up to 10 4 -10 9 copies/ml for swab samples [ 165 ]. A custom-made fidget spinner that rapidly concentrated pathogens in 1 ml samples of undiluted urine by more than 100-fold for the on-device colorimetric detection of bacterial load and pathogen identification was designed and fabricated ( Figure 5 c) [ 166 ].…”
Section: Micro/nano Devices For Point-of-care Testing Of Sars-cov-2mentioning
confidence: 99%
“…This mechanism serves as a particle sorter and concentrator and can drastically increase particle concentration in the small protrusion cavities by collecting particles from a fluid flow stream. Once isolated in the cavity, these particles can be analyzed through a variety of mechanisms [ 13 , 14 ] or altered through chemical reactions, temperature, or mechanical stimulation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such application is the use of integrated solid-state nanopores as a means of particle identification when particles translocate the pore [ 21 ]. Thin membranes are required for focused ion beam (FIB) nanopore drilling in order to achieve tight pore dimensions [ 16 ]. The concentration and isolation functionality of this platform offers an excellent way to position high numbers of samples directly under the pore.…”
Section: Introductionmentioning
confidence: 99%